New Attorney Bar Admission Ceremony in Wine Press Room - Watkins, Howard::::::::: (1988)
Fifth District Court of Appeal Clerk Kevin Swanson ; Standing: U.S. District Court Judge Dean Price and Justices James Ardaiz and Hollis Best